2020
DOI: 10.5530/ijmedph.2020.4.35
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Musculoskeletal Disorders among Public Sector Bank Employees of Mangaluru Region – A Cross-sectional Study

Abstract: Introduction: Certain professions predispose individuals to obesity and musculoskeletal disorders. Banking is one such sector where working involves sitting for prolonged times along with exposure to physical and psychosocial risk factors. Very few studies have been conducted in India in public sector bank settings, concerning these chronic conditions. This study intends to encourage further research in these areas. Objectives: This study aimed to determine the prevalence of obesity and MSDs. Its objectives we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A total of 8883 respondents were participated from 14 different countries. Five studies were conducted from India [ 11 , 24 , [27] , [28] , [29] ], four from Ethiopia [ 1 , 8 , 20 , 21 ], three from Iran [ 26 , 30 , 31 ], two from China [ 25 , 32 ], two from Malaysia [ 7 , 33 ], and one study each from Bangladesh [ 4 ], Egypt [ 9 ], Saudi Arabia [ 34 ], Ghana [ 23 ], Pakistan [ 35 ], Kuwait [ 6 ], Nigeria [ 36 ], Sri Lanka [ 37 ], and Estonia [ 38 ]. The prevalence of WMSDs was obtained from all studies [ 1 , 4 , [6] , [7] , [8] , [9] , 11 , 20 , 21 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ], while the data regarding to associated factors were also reported by all except two studies [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 8883 respondents were participated from 14 different countries. Five studies were conducted from India [ 11 , 24 , [27] , [28] , [29] ], four from Ethiopia [ 1 , 8 , 20 , 21 ], three from Iran [ 26 , 30 , 31 ], two from China [ 25 , 32 ], two from Malaysia [ 7 , 33 ], and one study each from Bangladesh [ 4 ], Egypt [ 9 ], Saudi Arabia [ 34 ], Ghana [ 23 ], Pakistan [ 35 ], Kuwait [ 6 ], Nigeria [ 36 ], Sri Lanka [ 37 ], and Estonia [ 38 ]. The prevalence of WMSDs was obtained from all studies [ 1 , 4 , [6] , [7] , [8] , [9] , 11 , 20 , 21 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ], while the data regarding to associated factors were also reported by all except two studies [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to a study report, lower back pain was one of the leading MSDs among computer user employees. Among 25 studies, 12 articles reported that lower back pain was the most prevalent MSD throughout the body [ 1 , 11 , [19] , [20] , [21] , 23 , 24 , 28 , 30 , 33 , 34 , 42 ]. Upper back pain was also one of the top-listed MSDs next to lower back and neck pain [ 1 , 4 , [6] , [7] , [8] , 11 , [20] , [21] , [22] , [23] , 25 , 28 , 30 , 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations